China's space policy-a historical review. (August 2016) - Chen, Yanping
Abstract: The political and economic climate in China has changed often and wildly since the country's space programme was founded. Nevertheless the programme has remained remarkably stable and achieved major successes. This article traces the programme's history in the context of the four major periods through which it has lived and offers an explanation of why and how it has survived so well: high-level government support, international prestige and committed personnel. The recent Tiananmen turmoil has not dimmed its progress and the programme looks set both to advance its space commercialization efforts in the short term and to develop a manned capability in the long term.